Clinicoepidemiological Pattern and Quality of Life Indices among Adult Males with Acne Vulgaris: A Hospital-based Cross-sectional Study - Ananya B. Reddy; Fathima Shafi; Malcolm Pinto; Spandana Prakash Hegde; Amina Asfiya (Archives of Medicine and Health Sciences)
Background and Aim: Adults with acne have been found to have a higher incidence of anxiety, depression, and suicidal ideation as compared to the general population. To the best of our knowledge, there is a dearth of studies assessing the quality of life among males with acne. This study explores the clinical patterns of acne with special emphasis on quality of life among adult males with acne vulgaris. Materials and Methods: All male patients visiting the dermatology outpatient department with acne were included after obtaining informed consent. Demographic data were recorded. Clinical assessment was done based on Global Acne Grading System (GAGS) and qualitative global acne scar grading. Assessment of quality of life was done using Dermatological Life Quality Index (DLQI) and Cardiff Acne Disability Index (CADI) in each patient. Results: Among 322 patients recruited in this study, 293 patients (91.3%) had mild acne, followed by 29 patients (8.7%) who had moderate acne as per GAGS score. The mean DLQI and CADI scores were 5.07 ± 5.0 and 4.0 ± 2.8, respectively. GAGS was found to have a significant correlation with CADI but not with DLQI. Conclusion: CADI score is an important tool which can enable dermatologists to assess the psychosocial burden of the disease in men with acne. This can enable the development of a comprehensive management plan which will enable better treatment and better quality of life in men with acne.